Identifikasi Fase Pertumbuhan Makroskopis dan Ciri Mikroskopis Jamur Leucoagaricus sp. - Yahya, Chesa Devi Aksa; Utami, Faiza; Puteri, Maulia Nauly Syahlina; Gyanika, Azzahra; Ritonga, Ahmad Rahazi Pangulu; Mahardhika, Wahyu Aji; Putra, Ivan Permana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Indonesia, with its tropical climate, harbors a rich diversity of macroscopic fungi, including wild mushrooms that thrive in various regions, one of which is the Oil Palm Forest area of IPB University, Dramaga. This study aimed to identify the macroscopic growth stages and microscopic characteristics of Leucoagaricus sp. found in the Oil Palm Forest of IPB University, Dramaga. The species was observed to grow in a humid environment, exhibiting three distinct fruiting body growth stages with characteristic coloration corresponding to each stage, and microscopic features including septate hyphae and basidiospores. The development of Leucoagaricus sp. is influenced by environmental factors and ecological interactions. Furthermore, Leucoagaricus sp. possesses therapeutic potential as a natural antimicrobial and antioxidant. This study highlights the importance of conserving and exploring wild fungi as valuable biological resources.